The Correlation between Body Mass Index (BMI) and Recovery Time on General Anesthesia Patient Using Endotracheal Tube (ET) - Maryadi, Adi; Rahmaya Nova Handayani; Eza Kemal Firdaus; Asmat Burhan (Global Indonesia Health Care (GOICARE), 2024)
Conscious recovery time is the time it takes for the patient to be removed from the conscious recovery room when the patient is fully conscious. Patients who are unconscious within more than 15 minutes are considered prolonged, even to respond to a stimulus in highly susceptible patients requires 30-45 minutes after general anesthesia drugs are stopped. One of the causes of lengthening the time to recover consciousness is the Body Mass Index (BMI) in patients which can increase the potential of anesthetic drugs given. The purpose of this study was to determine the relationship between Body Mass Index (BMI) and conscious recovery time in general anesthesia patients using Endotracheal Tube (ET) at RSUD Dr. Soedirman Kebumen. The method of ths study was correlation analitik with a cross-sectional approach. The sample of this study amounted to 48 respondents with consecutive sampling technique. Data analysis was carried out using the Kendall Tau test. The results of the study obtained 86.5% of respondents had a fast conscious recovery time (<15 minutes) and 13.5% of respondents had a prolonged conscious recovery time (>15 minutes). Of the results of the kendall tau correlation test obtained results with a significancy p value of 0.000 < 0.05 which means there is a relationship between the body's mass index to the recovery time of consciousness after general anesthesia with the endotracheal tube. The conclusion of this study is that majority of respondents who have a quick recovery time of less tha 15 minutes are respindents with a normal body mass index. Patient with a fat or obese BMI will receive a higher dose of anesthetic medication compared to patients in the thin category. When the anesthetic drug is given a higher concentration, the effect of the ansthetic drug will be longer.